STUDI NETNOGRAFI TAYANGAN "KISAH HILANGNYA 3 PENDAKI GUNUNG SLAMET 1985" CHANNEL RJL 5 - Alvin Praditya; Ibrahim Bali Pamungkas; Rahadyan Tajuddien (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The behavior of horror-themed enthusiasts who engage in malicious commenting online is regarded as a disease or social issue that we cannot control. Based on this premise, this research aims to determine the audience's response to the YouTube channel RJL 5 - Fajar Aditya, specifically regarding the show about the disappearance of 3 mountaineers on Mount Slamet in 1985. This study is closely related to the methodology of netnography, which includes research planning, data collection, interpretation, and adherence to ethical standards in data validity testing. Netnography utilizes internet communication as a data source to achieve an understanding of ethnography and the representation of cultural phenomena. The netnographic analysis conducted on the RJL 5 YouTube channel regarding the audience's response to "The Story of the Disappearance of 3 Mountaineers on Mount Slamet 1985" yielded several conclusions. Firstly, the audience is consistently amazed by the storytelling skills of Mr. Alex, which is an inherent cognitive aspect of the viewers. Secondly, the audience gains survival knowledge and appreciates Mr. Alex for his ability to survive when he was lost on Mount Slamet, receiving positive responses from the viewers. Thirdly, some viewers express a desire for the story of the disappearance of the 3 mountaineers on Mount Slamet in 1985 to be adapted into a film. Lastly, in addition to responses related to the Mount Slamet story, viewers often discuss unrelated topics in their comments to the content creator.